Flaviviridae replication organelles: oh, what a tangled web we weave - Paul, David; Bartenschlager, Ralf (Annual review of virology, 2015)
Replication of positive-strand RNA viruses occurs in tight association with reorganized host cell membranes. In a concerted fashion, viral and cellular factors generate distinct organelle-like structures, designated viral replication factories. These virus-induced compartments promote highly efficient genome replication, allow spatiotemporal coordination of the different steps of the viral replication cycle, and protect viral RNA from the hostile cytoplasmic environment. The combined use of ultrastructural and functional studies has greatly increased our understanding of the architecture and biogenesis of viral replication factories. Here, we review common concepts and distinct differences in replication organelle morphology and biogenesis within the Flaviviridae family, exemplified by dengue virus and hepatitis C virus. We discuss recent progress made in our understanding of the complex interplay between viral determinants and subverted cellular